Peningkatan Keterampilan Pengolahan Dokumen dan Data Menggunakan Microsoft Office bagi Siswa SMA - Reynaldi Furqoni; Ilsa Isnania; Faturrachman Al Kautsar; Salma Rodiah; Sanusi Sanusi; Vira Fitriza Fadli (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid growth of information technology demands high digital literacy from vocational students to prepare them for both higher education and the professional workforce. This community service (PkM) project aims to address the skill gaps in administrative applications among students at SMK PU Kabupaten Lebak. Observation revealed that students faced challenges in structure-formatting long academic documents, executing systematic functions in spreadsheet calculation, and constructing logical slides for communication. To solve these structural challenges, an intensive practical workshop method was established, integrating interactive lectures, direct computer laboratory practices, and individualized mentoring modules. This program thoroughly covered essential applications, including Microsoft Word for official reporting alignment, Microsoft Excel for computational data analysis, and Microsoft PowerPoint for dynamic visual communication. Evaluation was conducted using a rigorous pre-test and post-test measurement design. The empirical results demonstrated a substantial enhancement in digital capacity, where the class average test score significantly accelerated from 48.50% to 84.20%. Furthermore, qualitative responses confirmed a high level of learner participation and self-confidence. This intensive training successfully cultivated the critical technical proficiency required by vocational school graduates to successfully transition into complex technical environments.